QIRAAT IBNU KATHIR DAN IMPLIKASINYA TERHADAP TAFSIR - Jannnah, Aqilatul; Aziz, Azalia Wardha (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2023)
The diversity of reading the Qur'an or qira>'a>t existed at the time of the Prophet Muhammad SAW and received it from Jibril a.s. Then Prophet Muhammad SAW taught it to the companions of the Prophet, and the companions of the Prophet taught it to the tabiin. The development of qira>'a>t does not just stop as a variety of reading the Qur’an. However, qira>'a>t developed into a science and gave birth to qira>'a>t experts known as Imam of qira>'a>t. The Imam of qira>'a>t are known as their mutawa>tir qira>'a>t, namely qira>'a>t sab'ah. All of the existing qira>'a>t have their own similarities and differences. Likewise, qira>'a>t Imam Ibn Kathir who is one of the imams of qira>'a>t sab'ah. Qira>'a>t Imam Ibn Kathir in several verses, at first glance it only looks different in the pronunciation of reading the Qur'an. However, the difference in qira>'a>t is not only different in terms of pronunciation but also meaning. This can be identified from the aspect of the difference in qira>'a>t itself. As in the implications of Imam Ibn Kathir's qira>'a>t for interpretation, which consists of differences in harakat and syakl also i'rab which have implications for meaning, differences in character which have implications for meaning and writing and differences in al-ziyadah and al-nuqsan. Therefore, Imam Ibn Kathir's qira>'a>t does not only affect the pronunciation or reading, but also affects changes in meaning which have implications for interpretation.